3RD INTERNATIONAL FORUM “REDUCING CHILD MORTALITY – THE RUSSIAN EXPERIENCE OF UNIVERSAL PEDIATRIC CARE COVERAGE FOR CHILD POPULATION AS AN INSTRUMENT FOR ACHIEVING MILLENNIUM DEVELOPMENT GOALS” (Педиатрическая фармакология)
.